Comparative accuracy of the Clearing Technique, CBCT and Micro‐CT methods in studying the mesial root canal configuration of mandibular first molars - Ordinola‐Zapata, R.; Bramante, C. M.; Versiani, M. A.; Moldauer, B. I.; Topham, G.; Gutmann, J. L.; Nuñez, A.; Duarte, M. A. Hungaro; Abella, F. (International endodontic journal, 2017)
Aims To compare the accuracy of the clearing technique and cone beam computed tomography (CBCT) in the assessment of root canal configurations using micro‐computed tomography (micro‐CT) imaging system as the reference standard. Methodology Thirty‐two mesial roots of mandibular first molars, selected on the basis of micro‐CT scans (voxel size: 19.6 μm) and presenting several canal configurations, were evaluated using 2 CBCT scanners (voxels sizes: 120 μm and 150 μm) followed by the clearing technique. Two examiners analysed the data from each method and classified the anatomical configuration of the mesial canal according to Vertucci's system. Data were compared using Fisher's exact and chi‐square tests. Reliability for each assessment was verified by the kappa test, and significance level was set at 5%. Results Kappa value indicated a high level of agreement between the examiners. Detection of type I configurations was significantly lower in cleared teeth (P < 0.05), whilst type II root canals were detected in all specimens by both tests (P > 0.05). In mesial roots with variable anatomical configurations, CBCT and the clearing method were significantly less accurate than the reference standard (P < 0.05). Conclusion Within the tooth population studied, accuracy of identifying mesial root canal configuration was influenced greatly by the evaluation method and the type of anatomy. Detection of type I configurations in cleared teeth was significantly lower, whilst type II configurations were detected in all specimens by both methods. In mesial roots with variable anatomical configurations, neither CBCT nor clearing methods were accurate for detecting the actual root canal anatomy.